Puccini's Manon Lescaut - Puccini, Giacomo, 1858-1924 (Opera Journeys Pub., 2003)
A newly translated Libretto featuring foreign language/English side-by-side, and music examples interspersed throughout the text.
Libretto by Ruggiero Leoncavallo, Domenico Oliva, Luigi Mica, Giuseppe Giacosa, Luigi Illica, and Giulio Ricordi, after the novel by Abbé Prévost, L'Histoire du Chevalier des Grieux et de Manon Lescaut (1731).
Keywords: Puccini, Giacomo, -- 1858-1924. -- Manon Lescaut.; Manon Lescaut (Puccini, Giacomo); Operas -- Librettos.; Opéras -- Livrets.; MUSIC -- Genres & Styles -- Opera.; Operas -- Librettos